A Critique on the Book Methodology of Islamic Economics; An Institutional Reality Approach - Ali Saeedi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Methodology of Islamic Economics is a textbook for MA and PhD students of Islamic economics. Using the concept of institution, the author has tried to make a connection between the Shari'a rules, as matters of conventionals, and economic realities and concludes that differences of conventionals in Islamic societies and others, requires differences in social realities and so Islamic economics requires a different methodology. The author then examines a list of institutions derived from the Shari'a rules and how it affects social realities. The main drawback of the book is to move away from the methodology and there is almost no discussion about the evaluation of theories of Islamic economics or the criterion of the scientific nature of these theories. Much of the book discusses the differences between Islamic economics theories from those of neoclassical economics. The author has used some concepts of institutionalism without clarifying the relationship between institutionalism and Islamic economics. The critique of the foundations of neoclassical economics also relies on other schools of economics, including the German historical school and behavioral and institutional economics, while the author was expected to critique from the perspective of Islamic economics. It is suggested that the title of the book can be changed and the author can make a fundamental review of the book's topics in the next edition.